Some Economic Aspects of Egyptian Foreign Agricultural Trade of Grape Crop - Shehata, Gaber A. B.; Elsharkasy, Shaker E.; Khedra, Mosbah M.; Meky, Fouaad M. H.; Zahran, Hanan A. M. (Advances in Social Sciences Research Journal, 2023)
The grape crop is considered one of the main fruit crops in Egypt, which is grown for local production and export. Its fruitful area amounted to about 133.81 thousand feddan (Feddan = 0.42 hectare), representing about 9.28% of the total fruitful area of ​​​​about 1.44 million feddan, and the production reached about 1.30 million tons, which represents about 11.22% of the total fruit production amounting to about 11.59 million tons, and Egypt produces the equivalent of 6.49% of the total world production of grapes, and the value of Egypt’s grape exports amounted to about $ 131.07 million, which represents about 2.91% of the value of global production of grapes, which is about $ 10894.6 million in 2020. The research aims to identify the current production situation of the Egyptian grape crop, as well as to identify the current situation of exports of the Egyptian grape crop, in addition to measuring the export performance indicators of it, and to identify the importance of this crop as one of the productive and export crops, in addition to the possibility of developing or increasing exports. The research relied on the two methods of descriptive and quantitative analysis, using some indicators (market share, apparent comparative advantage, instability coefficient, market penetration coefficient), we find that the competitive advantage index has exceeded the one during the period (2000-2020), Which indicates the importance of this export crop. It was found from the results: that the annual growth rate in each of the total production and consumption, the quantity and price of export, and the value of exports of the Egyptian grape crop reached about 1.90%, 1.50%, 15.70%, 10.06%, and 20.30%, respectively during the period (2000-2020), and by studying the export performance indicators of the Egyptian grape crop using the competitive advantage index, we find that it has exceeded the one during the previous period, which indicates the importance of this crop as an important export crop. These countries are (Italy, South Africa, Turkey, Spain, Greece, Syria, Lebanon, Morocco, Israel, Tunisia) with rates of about (36.35%, 21.41%, 20.41%, 9.96%, 5.63%, 2.81%, 1.68%, 0.97%, 0.63% and 0.09%), respectively, during the same previous period. And by studying the most important world markets of the Egyptian grape exports were Netherlands, Germany, Belgium, Saudi Arabia, and other countries which amounting to about 15.02%, 11.77%, 3.64%, 1.90%, 41.16% respectively, during the same previous period. and by studying the market penetration coefficient for Egyptian grape exports during the average period (2000-2020), it was found that the most important of these countries are Netherlands, Belgium, Saudi Arabia, United Kingdom, Germany with rates of about 0.47%, 0.43%, 0.42%, 0.40%, 0.37%, meaning that each country obtains the previous percentage of its needs from the Egyptian grape crop, respectively, during the average of the previous period, and it is clear that the market penetration rate of the Dutch market has increased as an average for the previous period. And by studying the instability coefficient for the quantity of production, the quantity of exports, and the price and value of exports of the Egyptian grape crop, we find that the quantity of production and the quantity of exports were more stable than the price, while the value was the most volatile during the same previous period. By studying the market share of Egyptian grape exports to the most important importing countries (United Kingdom, Germany, Netherlands, Belgium, Saudi Arabia), it is clear that these percentages decreased during the study period between Egypt and those countries, as they reached about (5.94%, 1.69%, 3.23%, 3%, 2.07% and 2.75%, respectively, during the study period. In light of reviewing the various results of the study, a set of recommendations can be put forward that may benefit the makers of agricultural policy and internal or external marketing of Egyptian grapes to increase its production and exports to various global markets.